2021
DOI: 10.1016/j.omtn.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated m6A mRNA modification promotes esophageal cancer initiation and progression via Notch signaling pathway

Abstract: Esophageal cancer is a lethal malignancy with a high mortality rate, while the molecular mechanisms underlying esophageal cancer pathogenesis are still poorly understood. Here, we found that the N6-methyladenosine (m 6 A) methyltransferase-like 3 (METTL3) is significantly upregulated in esophageal squamous cell carcinoma (ESCC) and associated with poor patient prognosis. Depletion of METTL3 results in decreased ESCC growth and progression in vitro and in vivo. We further established ESCC initiation and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Another study showed that FTO is involved in oncogenesis of ESCA through upregulation of MMP13 ( 9 ). In addition, METTL3 may also promote ESCA proliferation and invasion by regulating multiple pathways, such as AKT ( 10 ), Notch ( 11 ), COL12A1/MAPK ( 12 ) and other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that FTO is involved in oncogenesis of ESCA through upregulation of MMP13 ( 9 ). In addition, METTL3 may also promote ESCA proliferation and invasion by regulating multiple pathways, such as AKT ( 10 ), Notch ( 11 ), COL12A1/MAPK ( 12 ) and other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the m6A regulators in esophageal cancer all play a cancer-promoting role, except for ALKBH5 [ 100 , 256 ]. The downstream targets that the m6A writer METTL3 regulates in esophageal cancer are GLS2 [ 257 ], p21 [ 258 ], Wnt/β-catenin [ 38 , 259 ], AKT [ 259 ], the EMT [ 259 ], and the Notch [ 260 ] signaling pathway. ALKBH5 plays dual roles in promoting and suppressing tumor growth in esophageal cancer.…”
Section: M6a and Cancersmentioning
confidence: 99%
“…METTL3 in human tissue is highly expressed and conserved, especially in the testes. Recent studies reported that METTL3 is significantly highly expressed in chronic myeloid leukemia ( Ianniello et al, 2021 ), thymic epithelial tumors ( Iaiza et al, 2021 ), esophageal cancer ( Han et al, 2021 ), and prostate cancer ( Chen et al, 2021b ), suggesting a close relationship with malignant tumor development. Previous studies also suggested that METTL3 is significantly up-regulated in BC.…”
Section: M6a Roles and Mechanisms In Bcmentioning
confidence: 99%